The cross-over to magnetostrophic convection in planetary dynamo systems. (15th March 2017) - Aurnou, J. M.; King, E. M.
Abstract : Global scale magnetostrophic balance, in which Lorentz and Coriolis forces comprise the leading-order force balance, has long been thought to describe the natural state of planetary dynamo systems. This argument arises from consideration of the linear theory of rotating magnetoconvection. Here we test this long-held tenet by directly comparing linear predictions against dynamo modelling results. This comparison shows that dynamo modelling results are not typically in the global magnetostrophic state predicted by linear theory. Then, in order to estimate at what scale (if any) magnetostrophic balance will arise in nonlinear dynamo systems, we carry out a simple scaling analysis of the Elsasser number Λ, yielding an improved estimate of the ratio of Lorentz and Coriolis forces. From this, we deduce that there is a magnetostrophic cross-over length scale, L X ≈ ( Λ o 2 / R m o ) D, where Λ o is the linear (or traditional) Elsasser number, Rm o is the system scale magnetic Reynolds number and D is the length scale of the system. On scales well aboveL X, magnetostrophic convection dynamics should not be possible. Only on scales smaller thanL X should it be possible for the convective behaviours to follow the predictions for the magnetostrophic branch of convection. BecauseL X is significantly smaller than the system scale in most dynamo models, their large-scale flows should be quasi-geostrophic, as is confirmed in many dynamo simulations. Estimating Λ o ≃1 and Rm o ≃10 3 in Earth's core, the cross-over scale is approximately 1/1000 that of the system scale, suggesting that magnetostrophic convection dynamics exists in the core only on small scales below those that can be characterized by geomagnetic observations.